Technological Prospective of Manufacturing for the Year 2030 - Alfaro-Marchant, M (Institute of Electrical and Electronics Engineers Inc., 2018)
The end of the fifth technological wave of Kondratieff implies great prospective changes for the society, our research was centralized in the technological prospective of the manufacture for the year 2030. The projections of the technological tendencies were developed by a committee of experts and evaluated by a heterogeneous group of specialists in manufacturing industry, government and academia using the Delphi method. The study made it possible to reveal projections with significant impact for the manufacture of the year 2030 corresponding to complex technological processes due to their transdisciplinary and multifactorial characteristics. Technological processes currently under development are established with a direct impact on the capacity to generate new jobs and the society s welfare; the accelerated automation of processes, services and manufacturing through artificial intelligence, nanotechnology and biotechnology will radically transform the world. © 2018 IEEE.